Spread of Mutant Middle East Respiratory Syndrome Coronavirus with Reduced Affinity to Human CD26 during the South Korean Outbreak - Yuri Kim; Shinhye Cheon; Chan-Ki Min; Kyung Mok Sohn; Ying Jin Kang; Young-Je Cha; Ju-Il Kang; Seong Kyu Han; Na-Young Ha; Gwanghun Kim; Abdimadiyeva Aigerim; Hyun Mu Shin; et al. (mBio, 2016)
ABSTRACT The newly emerging Middle East respiratory syndrome coronavirus (MERS-CoV) causes a severe respiratory infection with a high mortality rate (~35%). MERS-CoV has been a global threat due to continuous outbreaks in the Arabian peninsula and international spread by infected travelers since 2012. From May to July 2015, a large outbreak initiated by an infected traveler from the Arabian peninsula swept South Korea and resulted in 186 confirmed cases with 38 deaths (case fatality rate, 20.4%). Here, we show the rapid emergence and spread of a mutant MERS-CoV with reduced affinity to the human CD26 receptor during the South Korean outbreak. We isolated 13 new viral genomes from 14 infected patients treated at a hospital and found that 12 of these genomes possess a point mutation in the receptor-binding domain (RBD) of viral spike (S) protein. Specifically, 11 of these genomes have an I529T mutation in RBD, and 1 has a D510G mutation. Strikingly, both mutations result in reduced affinity of RBD to human CD26 compared to wild-type RBD, as measured by surface plasmon resonance analysis and cellular binding assay. Additionally, pseudotyped virus bearing an I529T mutation in S protein showed reduced entry into host cells compared to virus with wild-type S protein. These unexpected findings suggest that MERS-CoV adaptation during human-to-human spread may be driven by host immunological pressure such as neutralizing antibodies, resulting in reduced affinity to host receptor, and thereby impairs viral fitness and virulence, rather than positive selection for a better affinity to CD26. IMPORTANCE Recently, a large outbreak initiated by an MERS-CoV-infected traveler from the Middle East swept South Korea and resulted in 186 confirmed cases with 38 deaths. This is the largest outbreak outside the Middle East, and it raised strong concerns about the possible emergence of MERS-CoV mutations. Here, we isolated 13 new viral genomes and found that 12 of them possess a point mutation in the receptor-binding domain of viral spike protein, resulting in reduced affinity to the human cognate receptor, CD26, compared to the wild-type virus. These unexpected findings suggest that MERS-CoV adaptation in humans may be driven by host immunological pressure.